2023
DOI: 10.3390/ijms24021560
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Tomato Drought Tolerance by PHYTOCHROME A and B1B2 Mutations

Abstract: Drought stress is a severe environmental issue that threatens agriculture at a large scale. PHYTOCHROMES (PHYs) are important photoreceptors in plants that control plant growth and development and are involved in plant stress response. The aim of this study was to identify the role of PHYs in the tomato cv. ‘Moneymaker’ under drought conditions. The tomato genome contains five PHYs, among which mutant lines in tomato PHYA and PHYB (B1 and B2) were used. Compared to the WT, phyA and phyB1B2 mutants exhibited dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
2
3
0
Order By: Relevance
“…The results of the drought tolerance study based on leaf wilting showed significant genetic variation among tomato accessions for tolerance to water stress. The results were consistent with past studies that have reported genetic variation in tomatoes for drought tolerance based on leaf wilting traits [43]. Finding genetic variation and developing highly drought-tolerant cultivars is critical for sustainable agriculture, as drought is a major environmental stress that affects crop productivity and quality worldwide.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the drought tolerance study based on leaf wilting showed significant genetic variation among tomato accessions for tolerance to water stress. The results were consistent with past studies that have reported genetic variation in tomatoes for drought tolerance based on leaf wilting traits [43]. Finding genetic variation and developing highly drought-tolerant cultivars is critical for sustainable agriculture, as drought is a major environmental stress that affects crop productivity and quality worldwide.…”
Section: Discussionsupporting
confidence: 91%
“…Finding genetic variation and developing highly drought-tolerant cultivars is critical for sustainable agriculture, as drought is a major environmental stress that affects crop productivity and quality worldwide. This study identified tomato accessions PI 365956, PI 584456, PI 390510, and PI 370091 imported from Peru, United States, Ecuador, and Canada (Supplementary Table S1; Table 2), respectively, to exhibit slow wilting under dry conditions, showing greater tolerance to drought stress, as the similar reports by Cardoso et al (2022) [38], Abdellatif et al (2023) [43], and Pathan et al (2014) [44] They concluded that plant genotypes of tomato and soybean that maintained slow-wilting traits and less yield loss were drought-tolerant. The droughttolerant accessions identified based on leaf wilting characteristics in this study could serve as valuable parental lines.…”
Section: Discussionsupporting
confidence: 80%
“…The PHYB gene also modulates drought tolerance in tomato plants, particularly in phyB1 mutants. phyB1 plants demonstrated longer shoots and roots and high amounts of proline, glycine betaine, and phenylalanine concentrations in their tissues than WT plants [ 89 ]. The osmoprotectants proline and glycine-betaine have been found to boost cellular osmotic control in drought-resistant plants [ [89] , [90] , [91] ].…”
Section: Phytochrome Engineering For Improved Tolerance Under Various...mentioning
confidence: 99%
“…phyB1 plants demonstrated longer shoots and roots and high amounts of proline, glycine betaine, and phenylalanine concentrations in their tissues than WT plants [ 89 ]. The osmoprotectants proline and glycine-betaine have been found to boost cellular osmotic control in drought-resistant plants [ [89] , [90] , [91] ]. Under the escape route above, phytochromes function as drought stress mediators.…”
Section: Phytochrome Engineering For Improved Tolerance Under Various...mentioning
confidence: 99%
“…PHYs are involved in distinct aspects of plant water relations (Abdellatif et al, 2023), modulating responses to drought stress, one of the most severe constraints to plant performance and productivity (Seleiman et al, 2021). The specificity of PHYs to stress responses has become increasingly evident, especially as regards the phytochrome type B family (Gavassi et al, 2017; Silva‐Junior et al, 2020).…”
Section: Introductionmentioning
confidence: 99%